Analisis Profil Pelajar Pancasila Dalam Buku Cerita Bergambar Keteladanan Potre Koneng - Putri, Estin Muharromah Pratiwi; Rosyadi, Dede; Fajrin, Nilamsari Damayanti (JOURNAL OF EDUCATION FOR ALL, 2024)
In this era of rapid globalization, it is causing a character and moral crisis. To overcome this problem, the government is currently starting to implement an independent curriculum, which in its implementation includes a Pancasila Student Profile to instill student character based on Pancasila values. To apply it in a fun learning process, learning media is needed that can support the cultivation of the Pancasila Student Profile. One of them is by using picture storybook media. However, in selecting the media you also need to pay attention to whether there are values in the Pancasila Student Profile or not. Therefore, in this study the researcher will analyze the values in the Pancasila Student Profile in the picture story book "Potre Koneng". The aim is that the learning media of picture story books can be taken into consideration by teachers to be used in instilling students' character based on Pancasila values. The research approach in this study is to use a qualitative approach with descriptive research methods. The type of research is library research. Based on the results of the analysis, the illustrated story book "Potre Koneng" contains six dimensions of the Pancasila Student Profile, including the Dimension of Faith and Devotion to God Almighty and Having Noble Morals, the Critical Reasoning Dimension, the Creative Dimension, the Mutual Cooperation Dimension, the Independent Dimension, and the Diversity Dimension. Global. Therefore, this picture story book can be used as material for consideration by teachers.